Parafoveal processing during reading is reduced across a morphological boundary. - Drieghe D; Pollatsek A; Juhasz BJ; Rayner K; Drieghe, Denis; Pollatsek, Alexander; Juhasz, Barbara J; Rayner, Keith (Cognition, 2010)
A boundary change manipulation was implemented within a monomorphemic word (e.g., fountaom as a preview for fountain), where parallel processing should occur given adequate visual acuity, and within an unspaced compound (bathroan as a preview for bathroom), where some serial processing of the constituents is likely. Consistent with that hypothesis, there was no effect of the preview manipulation on fixation time on the 1st constituent of the compound, whereas there was on the corresponding letters of the monomorphemic word. There was also a larger preview disruption on gaze duration on the whole monomorphemic word than on the compound, suggesting more parallel processing within monomorphemic words.